Grading; some references to help teacher - Munjiana Munjiana (Esteem Journal of English Education Study Programme, 2018)
Abstract: Most of the teacher especially in Palembang or south Sumatera did not know about the topic discuss in here, the conclusion is they have to know and applicant the grading system as mentioned above, the principle or mechanics, kinds and general grading system used in many countries. In conclusion by grading the teacher could observe and see the result assessment given to their students having the result for further topics, so by grading the teacher hopefully could change their way or their perception towards the grading issued.